Strengthening Institutions for Urban and Metropolitan Management and Service Delivery : Philippines Urbanization Review Policy Notes - World Bank (World Bank, Washington, DC, 2017)
This policy note discusses strengthening institutions for urban and metropolitan management and service delivery and is part of a broader Philippines urbanization study. Strong institutions are critical to the effective management of cities, the delivery of efficient urban services and infrastructure, and the establishment of an enabling environment for business and job creation. Strong institutions are needed to design and support policies for land and housing markets, raise and equitably redistribute revenues, and promote a safe and sustainable urban environment both at the national and local levels. A number of underlying institutional and governance issues at national and metropolitan levels in the Philippines stand out as binding constraints which have limited the country from optimizing the benefits of urban development. Even as the share of the national population living in urban areas has expanded to around 50 percent, urbanization in the country has never been guided by a comprehensive urban development policy supported by a clearly defined institutional framework. Institutional fragmentation among various oversight and sectorial agencies at the national level has exacerbated the weak institutional environment for urban development. The continuing expansion and population growth of urban areas throughout the country heightens the urgency for adopting comprehensive urban policy and institutional reforms that will enable the country to harness the benefits of urban development and mitigate negative externalities. There are a number of key challenges related to governance and institutions that are hampering successful urbanization: (i) absence of a comprehensive national urban policy; (ii) absence of a lead agency for urban development; (iii) weaknesses in the fiscal decentralization framework; and (iv) metropolitan fragmentation and weak mechanisms for inter-jurisdictional coordination.